The agricultural R&D investment gap in Latin America and the Caribbean - Nin-Pratt, Alejandro; Falconi, César A. (International Food Policy Research Institute, 2018)
Given the importance of agricultural R&D investment to sustain agricultural growth in the future, this study looks at the state of agricultural R&D investment in LAC, with the goal of identifying the level of underinvestment in the region. To do this the study uses a new indicator, the ASTI Intensity Index (AII) to measure agricultural R&D intensity in Latin America and the Caribbean (LAC) and compares research intensity with that of other regions and between countries within the region. The index can be used to identify potential under investors, determine intensity gaps and quantify R&D investment needed to close this gap by comparing countries with similar characteristics. Results obtained using a sample of 100 countries including 29 LAC countries show that despite rapid growth in R&D investment after 2004, the region shows low levels of intensity and the largest R&D intensity gap when compared to other regions. Results also show large differences between countries in the region. The Southern Cone (Brazil, Argentina, Chile, Uruguay and Paraguay) is among the regions showing highest levels of research intensity globally. Low levels of R&D intensity in the region are explained mainly by countries in Central America and by Andean countries. Results also show that the intensity gap represents almost 75 percent of total R&D investment in 2012 and that the region will need to increase investment from $5 to $8.5 billion 2011 PPP to close the intensity gap.